Infrared broadband all-fiber light source based on high-concentration Er3+/Yb3+ composite double-clad fiber. (18th May 2017) - Denker, B I; Egorova, O N; Galagan, B I; Kamynin, V A; Ponosova, A A; Sverchkov, S E; Semjonov, S L; Tsvetkov, V B
Abstract: We report characteristics of an infrared broadband all-fiber light source based on a high-concentration Er 3+ /Yb 3+ co-doped phosphate core silica cladding fiber as a gain medium. The fiber blank was fabricated by the 'rod-in-tube' technique. The concentrations of rare-earth ions in a phosphate glass for the fiber core were 1.7  ×  10 21 cm −3 of Yb 3+ and 1.3  ×  10 20 cm −3 of Er 3+ . The source demonstrated a maximum output power about 20 mW with a fiber length of only 50 cm. Maximum bandwidth at the  −10 dB level was 16.39 nm at a fiber length of 80 cm. Results from experiment indicate that using composite fiber offers good possibilities in achieving a broadband emission with a gain medium length several times shorter than that of silica fibers.